Where have I got to? Associations of age at marriage with marital household assets in educated and uneducated women in lowland Nepal - Marphatia,Akanksha A.; Saville,Naomi M.; Manandhar,Dharma S.; Cortina-Borja,Mario; Wells,Jonathan C. K. (PeerJ, 2024)
Background Women’s underage marriage (<18 years) is associated with adverse maternal and child health outcomes. Poverty in the natal household has been widely considered to be a key risk factor for underage marriage, but the evidence base is unreliable. When investigating this issue, most studies use marital wealth inappropriately, as a proxy for wealth in the natal household. In contrast, we investigated whether the timing of women’s marriage was associated with the wealth of the households they marry into, and how this may vary by women’s education level. This approach allows us to explore a different set of research questions which help to understand the economic value placed on the timing of women’s marriage. Methods We used data on 3,102 women aged 12–34 years, surveyed within 1 year of marriage, from the cluster-randomized Low Birth Weight South Asia Trial in lowland rural Nepal. Linear mixed-effects regression models investigated independent associations of women’s marriage age and education level with marital household wealth, and their interactive effects. Models adjusted for marital household traits. We analysed the full sample, and then only the uneducated women, who comprised a substantial proportion in our sample. Results In the full sample, we found that each later year of women’s marriage was associated with 1.5% lower asset score for those with primary education, and with 0.3% and 1.3% higher asset score for those with lower secondary or secondary/higher education, respectively. For uneducated women, relative to marrying ≤14 years, marrying at 15, 16, 17 and ≥18 years was associated with 1.5%, 4.4%, 2.4% and 6.2% greater marital asset score respectively. Conclusion On average, marrying ≥18 years was associated with greater marital assets for secondary-educated women. There were only very modest benefits in terms of marital household wealth for delaying marriage beyond 16 years for uneducated women or those with low education. These findings elucidate potential trade-offs faced by families, including decisions over how much education, if any, to provide to daughters. They may help to understand the economic rationale underpinning the timing of marriage, and why early marriage remains common despite efforts to delay it.
Keywords: Women’s early marriage; Child marriage; Women’s education; Marital household wealth; Marital household assets; Rural lowland Nepal